Radiological and mineralogical studies on the coastal area between Port-Said and Damietta. Issue 1 (1st August 2022) - Osman, A. M.; Seif, R. A.; Attia, R. M.; El-Azab, A.; Khalifa, I. H.
Abstract: The study area constitutes the Eastern flank of the Nile Delta between longitudes, 31° 39' 9.2″–32° 20' 9.6″ E and latitudes 31° 37′13″-31° 0′ 54″N, in the shoreline between Port-Said and Damietta. The radioelement contents were measured by gamma-spectrometry using NaI-detector and were studied mineralogically using binuclear and Environmental Scanning Electron microscopes after separation of heavy minerals by heavy liquids. eU, eTh, RaeU and K contents in the studied sediments and sabkhas are ranged from (1-2 ppm), (3-17 ppm), (1-4 ppm) and (0.45-1.25 wt.%) with averages 1.34, 7.18, 1.89 ppm and 0.77 wt.%, respectively. The average of radioelement contents is lower than the international averages, while the average of eTh/eU ratio is higher. High eTh/eU ratio reflects the poor weathering, rapid deposition of these sediments and the dominance of detrital radioactive minerals such as xenotime, monazite and zircon. eU/RaeU ratio average (0.9), is lower than unity and indicate the disequilibrium in the studied coastal sediments, suggesting disequilibrium and uranium migration out. The heavy minerals are represented meanly by magnetite, ilmenite, zircon, rutile, garnet, monazite, pyroxene and amphibole.